Analisis Monitoring Dampak Pengukuran Variabilitas Suhu Lingkungan Solar Panel Off-Grid Pada Model Panel Monocrystalline - Wando Pratama Siregar, Regi; Satria, Habib (Riau Jurnal Teknik Informatika, 2025)
The utilization of solar energy in Medan city has not been optimal, which is a case that requires a solution. This is due to the lack of understanding of the working concept and the factors influencing the efficiency of power generated by solar panels. The research conducted in the Medan City area, North Sumatra, aims to determine the performance of the monocrystalline off-grid solar panel conversion in response to weather fluctuations. Based on the study of solar panel performance, the analysis shows that the power generated is influenced by key variables such as voltage, current, power, and light intensity (lux). The voltage of the solar panel remains stable throughout the day, ranging from 11.00 V to 19.80 V, with the peak occurring at 1:00 PM. The current varies, from 0.25 A in the morning to 5.90 A during the day. The peak power is recorded at 1:00 PM, reaching 116.82 Watts, along with the highest voltage and current. The intensity of sunlight (lux) also affects power, with the peak lux of 50,000 occurring at 1:00 PM. Overall, the solar panel performs best between 12:00 PM and 2:00 PM, while the output power decreases in the morning and evening.